ADDRESSING STUDENTS’ MORAL CRISIS IN THE DIGITAL ERA: ISLAMIC RELIGIOUS EDUCATION TEACHERS’ STRATEGIES AT SMA IT NUR HIDAYAH - Oktafiawa, Yurika; Mustofa, Triono Ali (International Journal of Cultural and Social Science, 2026)
The purpose of this study was to examine the strategies used by Islamic Religious Education (PAI) teachers at SMA IT Nur Hidayah in addressing students' moral crisis and to determine how well they are working to shape students' personalities in the digital age. This study employed a qualitative descriptive methodology, collecting data through observation, documentation, and interviews. Islamic Religious Education (PAI) teachers, guidance and counseling teachers, students, and purposively selected school administrators were among the research informants. Data reduction, data presentation, and conclusion drawing were used in the data analysis process. Triangulation of sources and strategies was used to ensure data quality. The results showed that students' moral crisis was characterized by a decline in respect, the use of impolite language, uncontrolled social behavior, and the negative influence of digital culture. To address this, Islamic Religious Education (PAI) teachers implemented systematic and sustainable strategies, including the (INSAN) program, fostering religious practices, strengthening social ethics, limiting gadget use, small-group guidance, and coaching-based development.